Effects of Probiotics on Serum Bilirubin Levels in Low –Birth-Weight Infants - Ahmad Shah Farhat; Nazli Parizadeh; Ashraf Mohammadzadeh; Monavar Afzalaghaei; Ezzat Khodashenas (Iranian Journal of Neonatology)
Background: Neonatal jaundice is frequently observed in preterm neonates, necessitating significant medical interventions, including phototherapy. This investigation assesses the impact of probiotics on serum bilirubin levels in preterm neonates with weights ranging from 1000 to 2500 grams. Methods: In this single-blind randomized clinical trial conducted at Imam Reza Hospital ( Mashhad, Iran) during 2019-2020 80 Low- Birth weight (LBW) neonates (1000-2500 g) were enrolled. The intervention group received 5 drops of probiotic daily for 5 consecutive days, initiated within 48 hours of birth. Transcutaneous bilirubin was measured daily for 7 days; serum bilirubin was assessed when transcutaneous values exceeded thresholds. Results: The trial comprised 40 neonates in the probiotic group and 40 in the control group. Statistical analysis revealed no significant baseline characteristic differences between the groups. Notably, in the subset of neonates without prior phototherapy, those administered showed a statistically significant reduction in bilirubin levels compared to controls (p value< 0.05). However, among neonates previously subjected to phototherapy, bilirubin levels, only on the sixth day, were statistically different between the probiotics and control groups (p value= 0.002) and bilirubin reduction did not significantly vary in the other days.Weight gain during the first week of the study, did not show a significant difference between two groups (p values were 0.392 and 0.632 in neonates with and without phototherapy, respectively). Conclusion: Probiotics, may effectively reduce serum bilirubin levels in preterm neonates, particularly those who have not undergone phototherapy.